Analysis of methodological approaches to the construction of dynamic systems of investment in information development - Chapran, Serhii (Technology audit and production reserves, 2021)
The object of research is theoretical and methodological approaches to mathematical modelling of dynamic nonlinear systems to ensure dynamic management of the investment process of information development of enterprises. Methodological aspects of building dynamic investment systems, maximizing the effectiveness of system interaction in information development are considered. One of the most problematic places is the formulation of the optimal approach to the methods of system analysis of decision management. The paper provides an opportunity to solve a wide range of problems, related to the flexible management of investment projects in the implementation of information technology. The study used the economic component of the formation of information resources, which contains an integral investment component of the information system. This is due to the fact that the proposed discreteness of this approach in the complex dynamics of the value of the information system contains partial estimates. Therefore, there should be a scheme of constant review of its value, which contains a dynamic component of the investment value of the information system with properties. The axiomatic approach was used in one of the most common approaches in the formal study of systems. The peculiarity is that the model is based on certain basic assumptions that do not require theoretical justification – on axioms. The study identified the main characteristics of the dynamic investment component of the system. Investments will have the properties of assessing information flows as part of information development. In particular, the research used approaches to modelling many solutions of the investment resources management process. The stages of modelling the process of dynamics and state of the system, implementation of the information support system are determined. This provides an opportunity to identify and assess the stages of investment, analysis of key risks and existing opportunities, defining strategies and methods of response, system typing. As well as the development and implementation of action plans to minimize the variability of investment areas and information structure.